Laparoscopic cost effective management of cholecystoduodenal fistula - Ratan, Md Ezharul Haque; Alam, Hasina; Karim, Md Abdul (Bangladesh Critical Care Journal, 2017)
Introduction: Contraindication to laparoscopic surgery is decreasing with time, expertise and innovation. One such uncommon condition is cholecystoduodenal fistula (CDF), now increasingly managed with laparoscopic technique. We are reporting eight such incidentally diagnosed cases during laparoscopic operation, which were successfully and cost-effectively managed with traditional laparoscopic instruments. Materials and Methods: During March 2008 to March 2017, 1500 patient underwent laparoscopic cholecystectomy for benign gall bladder condition or their complications, eight of these having chronic dyspeptic symptoms of gallstone, were found to have cholecystoduodenal fistula, intraoperatively. All cases were managed laparoscopically using common laparoscopic instruments without any special gadgets and extra costs. Medical records of eight cases were reviewed for age, sex, operative technique, intra and post-operative complications and length of stay in hospital. Results: Five patients were male and three were female with a mean age of 63 years. All of them had gall stones at abdominal ultrasound and cholecystoduodenal fistula were found intraoperatively. Fistula tract was dissected, cleaned and sealed with combination of intracorporeal simple transfixation ligation and interrupted stitches to invert the stump within the duodenal wall in transverse fashion. All eight had uneventful postoperative course with hospital stay of 4-7 (mean 5) days. Conclusion: In expert hands cholecystoduodenal fistula can successfully and safely be managed laparoscopically using common instruments and logistics with slight modification of open technique without extra cost. Bangladesh Crit Care J September 2017; 5(2): 110-112